The Australian Genera of Mymaridae (Hymenoptera: Chalcidoidea) - Lin, Nai-Quan; Huber, John T.; la Salle, John (Zootaxa, 2007)
The genera of Mymaridae occurring in Australia are keyed and a diagnosis for each is given. Forty-five nominal genera are recognized, including three new ones: Kompsomymar Lin and Huber, gen. nov., with type species K. bicoloratum Lin and Huber, sp. nov., Cleruchoides Lin and Huber, gen. nov., with type species C. noackae Lin and Huber, sp. nov., and Parastethynium Lin and Huber, gen. nov., with type species Parastethynium maxwelli (Girault), comb. nov. from Stethynium. The Australian genera are placed in twelve informal groups. Three new generic synonymies are proposed: Haplochaeta, syn. nov. under Cleruchus, Idiocentrus, syn. nov. under Paranaphoidea, and Nesetaerus syn. nov. under Australomymar. Twenty-six new combinations, are proposed: Allanagrus aurum (Girault), A. gladius (Girault) and A. mayeri (Girault) from Stethynium; Arescon nigriceps (Girault) from Anthemus; Australomymar gressitti (Doutt) from Nesetaerus and A. incerta (Girault) from Polynemoidea; Ceratanaphes laplacei (Girault) and C. wallacei (Girault) from Erythmelus; Cleruchus schilleri (Girault) and C. tintoreti (Girault) from Erythmelus, and Cleruchus mandibularis (Noyes and Valentine) from Haplochaeta; Erythmelus emersoni (Girault) from Anthemus; Gonatocerus aureinotum (Dodd), G. bellus (Girault), G. centaurus (Girault), G. citriscapus (Girault), G. flavipes (Girault), G. gigas (Girault), G. ignipes (Girault), G. iona (Girault); G. mirus (Girault), and G. prometheus (Girault) from Ooctonus; Mimalaptus victoriae (Girault) from Dicopus; Paranaphoidea harveyi (Girault) from Erythmelus; Pseudanaphes lincolni (Girault) and P. particoxae (Girault) from Polynemoidea. The species occurring in Australia are listed for each genus and their type localities are given.